Age-associated global DNA hypermethylation augments the sensitivity of hearts towards ischemia-reperfusion injury - Boovarahan, Sri Rahavi; Ali, Nemat; AlAsmari, Abdullah F.; Alameen, Alaa Alnoor; Khan, Rehan; Kurian, Gino A. (Frontiers in Genetics, 2022)
Most pre-clinical studies in cardiac ischemia-reperfusion injury (I/R) are carried out in young or old animals, which does not cater to the adult age in humans who encounter I/R. Not many studies in the literature are available that emphasize the sensitivity of the adult heart to injury from the young heart, where there exist distinct alterations in DNA methylation and mitochondrial function that contribute to injury. In the present study, we utilized young (8 weeks old) and adult (24 weeks old) rat hearts to evaluate distinct DNA methylation alterations that contribute to I/R injury. The cardiac basal level physiological activity and the ultrastructure in young and adult rat hearts were insignificantly changed from normal. But the DNA hypermethylation and expression level of mitochondrial genes were slightly higher in adult rat hearts. The consequential effect of these changes was measured in the I/R heart to understand its response to additional stress. Accordingly, we noted an increase in global DNA hypermethylation levels by 40% and 62% in young and adult I/R hearts, respectively, from their respective control. Subsequently, a decline in mitochondrial genes (ND1, ND4L, ND6, CytB, COX1, COX2 and ATP8) that regulate cardiac contractility was observed in adult I/R hearts. These changes, in turn, reduced hemodynamics (Rate pressure product) by 51% and 32% in adult and young I/R hearts, respectively from their controls. Besides, the I/R-linked infarct size was higher in adult hearts (58%) than in young hearts (37%). Correlation analysis showed a significant negative correlation of global DNA methylation with the MT-ND1 expression (r=-0.7591), MFN2 expression (r=-0.8561) and cardiac RPP (r=-0.8015) in adult I/R hearts. Based on the above observations, we concluded that age promoted DNA methylation and deteriorated cardiac responsive ability to resist I/R injury